2020
DOI: 10.3390/ijerph17218073
|View full text |Cite
|
Sign up to set email alerts
|

Transmission and Long-Term Colonization Patterns of Staphylococcus aureus in a Nursing Home

Abstract: Nursing homes might create an environment favorable for the transmission of Staphylococcus aureus because of the presence of hospitalized elderly, overcrowding and close contacts among people. We aimed at identifying risk factors for S. aureus colonization and determining the genetic relatedness of isolates demonstrating transmission among people. We investigated 736 swab samples from 92 residents and personnel for the presence of S. aureus. Swabs from anterior nares and throat were collected quarterly (2018) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
3
0
1
Order By: Relevance
“…Our present data show that the geographic area of our study (an ~50 km-radius area in southeast Michigan including the Detroit metropolitan area, its suburbs, and semi-rural locations at its outskirts) broadly fits into this pattern. A seasonal increase in MRSA colonization has recently been observed in a NH in Europe ( 12 ), as well as in healthy young populations ( 13 ). Reports from settings other than NHs are still very much relevant to NHs due to increased risk of introduction, especially in view of the current trends of diminishing length of stay and increase of resident turnover and new admissions.…”
Section: Discussionmentioning
confidence: 99%
“…Our present data show that the geographic area of our study (an ~50 km-radius area in southeast Michigan including the Detroit metropolitan area, its suburbs, and semi-rural locations at its outskirts) broadly fits into this pattern. A seasonal increase in MRSA colonization has recently been observed in a NH in Europe ( 12 ), as well as in healthy young populations ( 13 ). Reports from settings other than NHs are still very much relevant to NHs due to increased risk of introduction, especially in view of the current trends of diminishing length of stay and increase of resident turnover and new admissions.…”
Section: Discussionmentioning
confidence: 99%
“…Microbiological sampling was performed quarterly during the year 2018 for almost all of the participants (92/101). The technique of collecting the samples as well as the methods used for identification of S. aureus and the detection of methicillin resistance were described in detail previously [ 40 ]. The study was approved by the Bioethics Committee at the Medical University of Lublin, Poland (KE 0254/59/2016).…”
Section: Methodsmentioning
confidence: 99%
“…Over the years, the MRSA colonization rate, producing infections, has dramatically increased among different populations, the most susceptible being children and elderly >85 years of age. 10 , 11 As such, active screening of MRSA strains has become both necessary and urgent. In this study, we demonstrated that the active screening of nasal vestibular swabs in ICU patients can successfully achieve early detection, early intervention, and early treatment of hospitalized patients.…”
Section: Introductionmentioning
confidence: 99%